Anatomical significance of a posterior horn of medial meniscus: the relationship between its radial tear and cartilage degradation of joint surface - Kan, A.; Oshida, M.; Oshida, S.; Imada, M.; Nakagawa, T.; Okinaga, S. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2010)
Background Traumatic injury and surgical meniscectomy of a medial meniscus are known to cause subsequent knee osteoarthritis. However, the difference in the prevalence of osteoarthritis caused by the individual type of the medial meniscal tear has not been elucidated. The aim of this study was to investigate what type of tear is predominantly responsible for the degradation of articular cartilage in the medial compartment of knee joints.